Stability in Flowering, Flushing, and Fruiting Characters of 21 Potential Cacao Clones in ICCRI Collection - Indah Anita Sari; Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Flowering character and flowering intensity can be used to estimate productivity and it is important for supporting breeding activity especially for pollination program. This research was aimed to study the stability of character of flushing, flowering and fruiting on different cocoa clones (genetic). The research was done at Kaliwining Research Station, Indonesian Coffee and Cocoa Research Institute, Jember. There were 21 clones; KW 422, KW 426, KW 427, KW 425, KW 523, KW 062, KW 084, KW 094, KW 162, KW 163, KW 165, KW 219, KW 235, KW 236, KW 265, KW 005, KW 292, KW 570, KW 514, KW 516, and KW 617. Flowering intencity, fruiting, and flushing were observed. The result of the study showed that KW 084 was the most stable clone for fruiting. KW 235 had high pod number in April. KW 426, KW 427, KW 523, and Sulawesi 2 had high pod number in March and June. KW 219 and KW 516 had the lowest pod number. Low pod number did not occur in March until June. Flowering and flushing on all genotypes showed the stability value with IPCA value nearly zero. KW 094 showed high flowering intensity in October. High flushing intensity occurred in January and July, the lower one in April and August. Key words: Stability analysis, flushing, flowering, fruiting, cocoa clones